MODERN ANTIMICROBIAL MATERIALS WITH PROLONGED MEDICATIVE QUALITIES IN OPHTHALMOLOGY - Nazarchuk, G.G. (World of Medicine and Biology, 2016)
Antiseptic properties of nylon, impregnated with antimicrobial composition, its clinical effectiveness in infectious complications’ prevention were evaluated. We found, that in 360 hours of decamehtoxin desorbtion from the nylon’s (9/0) surfase there is 1,491 mkg/mm2 decamehtoxin in the solution. According to the results of the research, advantages of the antimicrobial nylon 9/0 in infected perforating corneoscleral wounds were found: the colonisation level and frequency of post operation purulent-inflammatory complications were lower in comparison with the usage of traditional nylon (р
Keywords: suture material; nylon; decamehtoxin; corneoscleral wound; eyelid wound; S. aureus